Effect of Gamma Radiation on Callus Induction and Plant Regeneration of four Wheats Triticum aestivum L. Genotypes - Baghdad Science Journal (مجلة بغداد للعلوم)
The effect of gamma radiation at the doses (0 , 5 , 10 or 15 ) Gray on the callus of four Triticum aestivum immature embryos genotypes (AL-Hashmiya , AL-Noor AL-Zahraa and AL-Mellad ) were studied . The fresh and dry weight for callus and shoot tips beside numbers and lengths of the shoots were used as indicators after 8 weeks .